2017
DOI: 10.4103/ijo.ijo_810_16
|View full text |Cite
|
Sign up to set email alerts
|

Drug-resistant coagulase-negative staphylococcal endophthalmitis following dexamethasone intravitreal implant

Abstract: A 60-year-old female came to our hospital with defective vision due to persistent diabetic macular edema and was treated with intravitreal ozurdex implant in the right eye. Three days later, the patient presented with diminution of vision, ocular pain, congestion, and hypopyon with no fundus view. B-scan ultrasonography showed vitritis, and diagnosis of endophthalmitis was made. Subsequently, 25-gauge pars plana vitrectomy was performed along with intravitreal vancomycin and amikacin and removal of implant. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 10 publications
(13 reference statements)
1
18
0
Order By: Relevance
“…At presentation, anterior segment inflammation was variable among cases. Hypopyon and fibrinoid membranes were present in three of the five cases presenting acutely, [2][3][4] and in none, including the current case, presenting subacutely. 6 In all cases, significant vitreous inflammation obscuring view to the posterior segment was observed.…”
Section: Discussionmentioning
confidence: 45%
“…At presentation, anterior segment inflammation was variable among cases. Hypopyon and fibrinoid membranes were present in three of the five cases presenting acutely, [2][3][4] and in none, including the current case, presenting subacutely. 6 In all cases, significant vitreous inflammation obscuring view to the posterior segment was observed.…”
Section: Discussionmentioning
confidence: 45%
“…Final visual acuity of 6/36 in our case was better than all other Ozurdex ® endophthalmitis cases from international literature which had a maximum gain in vision of 6/60. [1278]…”
Section: Resultsmentioning
confidence: 99%
“…We have not removed the implant initially, though many case reports highlighted the importance of Ozurdex ® removal. [789] We based our decision of not removing the implant on Stem et al . study which showed that is not necessary in all cases to perform vitrectomy or to remove the dexamethasone implant.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the injection setting and antibiotic prophylaxis, prefilled syringes as well as the large-gauge needles used in long-term release devices might also affect EO incidence [39][40][41]. In our study, ranibizumab and conbercept were packaged in a glass vial and aspirated with a large bore needle before injection.…”
Section: Discussionmentioning
confidence: 96%